Washington View: New tax plan provides little cheer for education. (February 2018) - Ferguson, Maria
The tax bills passed by the US House and Senate went after K-12 and postsecondary education in equal measure, undermining educational opportunities at nearly every turn. The author explains how changes to a long-standing tax deduction affecting state and local taxes could affect school districts, the likelihood that low-income families will benefit from new opportunities to use 529 savings plan for private school educations, and the ways in which tax changes could affect graduate students .